Reid Bryson: The crisis climatologist. (25th October 2021) - Naylor, Robert Luke
Abstract: Reid Allen Bryson (1920–2008) was a forceful orator who consistently fought against institutional pressures to get his messages out to the public. In the 1960s, Bryson was a leader in the wider academic turn toward politically charged interdisciplinarianism. To the dismay of many of his colleagues, he publicly made climatological prognoses in the 1970s, becoming a significant figure in the media landscape. He was not swayed by the arguments for global warming, even as the framing became the recognized face of climate change in the late 1980s. By examining the controversies that Bryson instigated and the currents that he swam against, we can see the wider community crystallizing and promoting positions that may have previously gone unstated. In addition, Bryson's personal contribution to the rise of climate discourse has been underexplored in the historical literature. Bryson was instrumental in bringing climate onto the political radar during the World Food Crisis of 1973, shocking both the US and Canadian political establishments into paying more attention to the issue. Bryson's narrative linking climate change to both food supply and a series of climate anomalies in the 1970s remained predominant in the first World Climate Conference of 1979. Bryson also helped break a seal on climatologists speaking directly to the media, leading to unprecedented climate discourse in the 1970s and giving climate change a springboard to become one of the defining issues of the 21st century. This article is categorized under: Climate, History, Society, Culture > Thought Leaders Abstract : Reid Bryson was a charismatic orator who helped spearhead the charge to bring climate change to a public audience in the 1970s.